Comparison of acoustic structures between heads of a narrow-ridged finless porpoise fetus and its mother - Song, Zhongchang; Zhang, Yu; Wang, Xianyan; Wei, Chong; Berggren, Per (OXFORD UNIV PRESS INC, 2016)
Computed tomography (CT) was used to compare the tissue structures involved in sound production and reception in a fetus and its maternal body of a female finless porpoise ( Neophocaena asiaorientalis sunameri ) found stranded at Huian, Fujian Province, China, in April 2014. Qualitative assessment of the CT images revealed the physical development of main acoustic tissues including melon, blubber, mandibular fat, muscle, and connective tissue in a 10-month old fetus. Compared to the maternal body, the cranium of the fetus was not enclosed, air sacs and nasal meatus were both absent, and the maxilla was much thinner. Furthermore, Hounsfield unit (HU) measurements from CT scanning were used to quantify the difference between the fetus and its maternal body for melon, blubber, mandibular fat, muscle, and connective tissue. Statistical analyses revealed significant differences in HU between all 5 structures melon, blubber, mandibular fat, muscle, and connective tissue ( P < 0.001) both in the fetus and maternal body. The median HU values of melon, blubber, mandibular fat, and muscle in the fetus (−61.0, −74.0, −24.0, and 25.0, respectively) were higher than those recorded in the maternal body (−85.0, −85.0, −69.0, and 12.0, respectively). However, the median HU value of connective tissue (50.0) in the fetus was lower than that recorded in the maternal body (60.0). The results show that the acoustic tissue structures were not fully developed in the fetus and depending on the actual age of the fetus the structures may not be fully formed by the time of birth. Further studies are needed to determine at what age finless porpoise calves have fully developed the tissue structures needed to produce and use ultrasound beams for echolocation.